2017
DOI: 10.1523/jneurosci.4505-14.2017
|View full text |Cite
|
Sign up to set email alerts
|

Does the Superior Colliculus Control Perceptual Sensitivity or Choice Bias during Attention? Evidence from a Multialternative Decision Framework

Abstract: Distinct networks in the forebrain and the midbrain coordinate to control spatial attention. The critical involvement of the superior colliculus (SC)-the central structure in the midbrain network-in visuospatial attention has been shown by four seminal, published studies in monkeys (Macaca mulatta) performing multialternative tasks. However, due to the lack of a mechanistic framework for interpreting behavioral data in such tasks, the nature of the SC's contribution to attention remains unclear. Here we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 52 publications
3
98
0
Order By: Relevance
“…A modeling study of behavioral data from monkeys engaged in attention demanding tasks indicated that the effects of SC inactivations are accounted for best by a disruption in the routing of visual information in the forebrain [20]. The results presented in this study are consistent with OT lesions having the same effect in birds.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…A modeling study of behavioral data from monkeys engaged in attention demanding tasks indicated that the effects of SC inactivations are accounted for best by a disruption in the routing of visual information in the forebrain [20]. The results presented in this study are consistent with OT lesions having the same effect in birds.…”
Section: Resultssupporting
confidence: 81%
“…A second possibility is that the OT lesions interfered with the routing of orientation information from the Wulst to decision networks that guide behavioral choice. A recent modeling study indicates that, in monkeys, the signal that ascends from the SC to the thalamus exerts such a routing effect on visual information in the forebrain [20]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, activity in sensory cortices correlates not only with sensory stimuli but also with motor planning 6,7 , movement 8 , upcoming behavioral reports [9][10][11][12][13][14] , spatial attention 15,16 and reward 17 . Similarly, in motor regions such as the deep layers of the superior colliculus 18 , activity correlates with aspects of decision making and other cognitive functions 5,[19][20][21][22][23] . The brain regions implicated to date in sensory-guided behavior include neocortex, basal ganglia, thalamus, and midbrain.…”
mentioning
confidence: 99%
“…These are, in order: (i) the cued location (Cu), (ii) the location in an adjacent quadrant, ipsilateral (Ip) or (iii) contralateral (Co) to the cue, and (iv) the location in the quadrant diagonally opposite to the cue (Op). The behavioral responses in the 5x5 contingency table were analyzed with a multidimensional signal detection model, the m-ADC model (36)(37)(38), to quantify psychophysical parameters (sensitivity and bias) at each location. In Figure 1C we show a schematic of a twodimensional (2-ADC) model, for illustrative purposes, although these data were analyzed with a fourdimensional (4-ADC) model (see Methods).…”
Section: A Change Detection Task Protocol: After An Initial Fixationmentioning
confidence: 99%
“…Because a salient exogenous cue also suppresses visual processing of stimulus information, we designed two post-cue control conditions which permitted isolating pre-cueing attentional effects from visual interference effects of the cue. Subjects' behavior was analyzed with a recently developed multidimensional signal detection model (36)(37)(38) that permitted quantifying exogenous cueing effects on sensitivity and bias at each location. The results reveal key dissociations between sensitivity and bias changes induced by exogenous cueing, and provide mechanistic insights into how exogenous cueing systematically facilitates behavioral accuracies and reaction times by modulating sensitivity and bias.…”
Section: Introductionmentioning
confidence: 99%